Transition to Formality and Structural Transformation Challenges and Policy Options. - Islam, Iyanatul, 1953-; Lapeyre, Frédéric, 1967- (International Labour Organisation (ILO), 2020)
The book examines new forms of informality in developed and developing countries, and how our policies can be improved to respond to new evolving realities.